Work-life-balance and employee performance in the Nigeria correctional service, Akwa Ibom State Nigeria correctional service - Uwa, Kingsley Lazarus (Direct Research Journal of Management and Strategic Studies, 2025)
This study examines the relationship between work-life-balance and employee performance in the Nigeria Correctional Service, Akwa Ibom State. Two hypotheses were formulated in line with the research objectives. The descriptive survey research design was adopted for the study and a sample size of eighty eight (88) respondents were drawn from a population of one hundred and thirteen (113) using Taro Yamani’s formula for sample size determination. The major instrument for data collection was a structured questionnaire administered to the respondents and the data collected were analyzed using simple percentage and Ordinal Logistic Regression Analysis. The results of the findings revealed that, there was a significant positive relationship between variables of Work-life Balance (leave policy, (????1) = 0.624, family responsibility (????4) = 1.830 and organizational performance 0.620 in the Nigeria Correctional Service Akwa Ibom State. Based on the findings of the analyses, all the proxies of Work-life Balance had significant positive relationship with Employee performance. Consequently, it is recommended that leave policy should be made available to employees for effective and efficient work delivery. Also, as a way of motivating and appreciating the employees, holidays and vacations where employees and their families would be shown some sort of appreciation should be made available. Besides, work should be designed in such a way that will reduce and cushion the effect of stress on the employees for effective delivery.